A phosphoric acid-based electrolyte additive and preparation method thereof
By using phosphate-based electrolyte additives in lithium batteries, combining lithium alginate and specific structure compounds, the problems of electrolyte conductivity and electrode corrosion are solved, higher cycling performance and conductivity are achieved, and flame retardant performance is enhanced.
Patent Information
- Application Number
- CN202411239986.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The conductivity of the electrolyte in existing lithium batteries is not as good as that of the electrolyte, and the electrodes are easily corroded by the electrolyte, resulting in insufficient cycling performance and conductivity.
Using phosphate-based electrolyte additives, a large number of lithium ions are provided by combining lithium alginate and compounds of specific structures (compounds represented by formula I), forming a good ion channel, improving conductivity, and forming a SEI film layer through a quaternary ammonium salt structure to prevent electrode corrosion.
It significantly improves the circulation performance and conductivity of lithium batteries, prevents electrode corrosion, and enhances the flame retardant performance of the electrolyte.
Smart Images

Figure SMS_16 
Figure QLYQS_1 
Figure QLYQS_4
Abstract
Description
Technical Field
[0001] The invention relates to heterocyclic compounds, and in particular to a phosphoric acid-based electrolyte additive and a preparation method thereof. Background Art
[0002] With the population growth and the continuous development of human civilization, fossil-based energy resources are becoming increasingly scarce, but the demand for energy is increasing. The most important thing now is to solve the problem of energy supply. Renewable energy is a breakthrough technological achievement in the energy field in recent years, but it also requires a renewable cycle and cannot be supplied continuously. The transportation industry is a field with a large amount of energy utilization. With the continuous development of the transportation industry, new energy vehicles have replaced some fuel vehicles, reducing environmental pollution and meeting the strategic goal of sustainable development.
[0003] Lithium-ion batteries are one of the most popular rechargeable batteries today, occupying the application market in many fields. Lithium-ion batteries have the following advantages: (1) Higher energy density: They can store more energy in a relatively small volume, which makes lithium-ion batteries particularly popular in the automotive field because they can provide longer driving range; (2) Longer service life: They can undergo multiple charge and discharge cycles without significant performance loss; (3) Faster charging speed; (4) Lighter: In the automotive field, lightweight batteries can reduce the weight of the entire vehicle, improve fuel efficiency and driving performance; (5) Environmental protection: Lithium-ion batteries do not contain toxic substances such as lead, fluorine, and mercury, and very little gas is released during use, which does not pollute the environment. Therefore, research on lithium batteries has gradually become popular.
[0004] Lithium batteries are mainly composed of four parts: positive electrode, negative electrode, separator and electrolyte. When the lithium battery is charged, lithium ions will be removed from the positive electrode and transferred to the negative electrode through the electrolyte. When the lithium battery is discharged, the lithium ions return to the positive electrode. The positive electrode material of lithium batteries currently uses lithium iron phosphate as the main material, which has good stability but low conductivity. The negative electrode material currently uses graphite as the main material, which has low cost, abundant resources and high energy density, but it can react with the electrolyte to cause the growth of lithium dendrites.
[0005] The electrolyte is the most important component in lithium batteries, which can affect the performance of the entire lithium battery. There are two types of electrolyte solvents, namely cyclic and linear. Common cyclic solvents are ethylene carbonate and propylene carbonate, and common linear solvents are dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate. The dielectric constant of the solvent is one of the main factors affecting the conductivity of lithium batteries. The lithium salt in the electrolyte is the main component for providing lithium ions. Common lithium salts include lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonylimide) and lithium bis(fluorosulfonylimide). In addition, in order to improve the comprehensive performance of lithium batteries, some additives are often added to the electrolyte to enhance the performance.
[0006] The electrolyte is flammable and can cause some safety issues, so researchers have developed an electrolyte that can solve this problem. However, the conductivity of the electrolyte is not as good as that of the electrolyte. This problem is still one of the important issues that the lithium battery industry must first break through and solve. In addition, there are some other issues such as the cycle performance of lithium batteries that still need to be solved.
[0007] In order to make up for the above problems, researchers often add some additives to the electrolyte / substance, such as CN115241532B discloses "electrolyte additives, electrolytes and lithium batteries". The electrolyte additive is a lithium salt anionic surfactant, which is rich in lithium ions and acts as an ion migration channel, significantly improving the cycle performance of lithium batteries. For example, CN114530629B discloses "a solid electrolyte and its additive preparation and application". The electrolyte additive in the patent is a polymer with excellent conductivity and thermal stability, and also has the characteristics of high-temperature cycle stability. For example, CN114430042B discloses "a lithium alginate for lithium battery additives and its preparation method and application". A self-made lithium alginate can be used as an additive in the preparation of positive and negative electrode materials of lithium batteries to improve the battery cycle performance and safety performance. For example, CN102789902A discloses "electrolyte additives, electrolytes and solar cells". In this patent, a self-made electrolyte additive is made, the synthesis steps are simple, and it can be well used in dye-sensitized solar cells to improve the stability of dye-sensitized solar cells.
[0008] However, none of the above-mentioned patents mentions or solves the problem of how to improve the conductivity of lithium batteries while improving the cycle performance of lithium batteries and preventing the electrodes from being corroded by the electrolyte.
[0009] Therefore, it is urgent to develop a phosphoric acid-based electrolyte additive that can improve battery cycle performance, prevent electrode corrosion, improve the flame retardancy of phosphoric acid-based electrolytes and improve battery conductivity. Summary of the invention
[0010] In view of the shortcomings of the prior art, the present invention provides a phosphoric acid-based electrolyte additive and a preparation method thereof. The phosphoric acid-based electrolyte additive of the present invention can improve battery cycle performance, prevent electrode corrosion, improve phosphoric acid-based electrolyte flame retardancy and improve battery conductivity.
[0011] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0012] On one hand, the present invention provides a phosphoric acid-based electrolyte additive, comprising the following raw materials: a phosphate compound, lithium alginate, a compound represented by formula I, and a solvent, wherein the mass ratio of the phosphate compound, lithium alginate, the compound represented by formula I, and the solvent is (0.3-0.5):1:(1.5-2.5):(6-10);
[0013] The structure of the compound shown in Formula I is:
[0014] (I), where R is , It is a bond connecting the amine group, R1, R2, and R3 are independently C1~C3 alkyl hydroxyl groups, and R4, R5, and R6 are independently C1~C4 alkyl groups.
[0015] The applicant found in the research that the functions of the currently commercially available phosphate-based electrolyte additives are relatively simple, while the electrolyte additive of the present application is compounded by using lithium alginate and the compound shown in formula I. Lithium alginate and the compound shown in formula I can provide a large amount of lithium ions, provide a good ion channel for the electrolyte, and improve the conductivity of the lithium battery. In addition, the phosphate-based electrolyte additive of the present application can also prevent the electrode from being corroded by the electrolyte, and enhance the flame retardant and cycle performance of the electrolyte. The reason may be that, on the first aspect, the compound structure shown in formula I contains a large amount of hydroxyl groups, which can adsorb lithium ions well and provide an additional pathway for the transport of lithium ions, making its flux more uniform; on the second aspect, since the compound structure shown in formula I contains a large amount of quaternary ammonium salt structure, it can be loaded on the surface of the electrode to form an SEI film layer to prevent it from being corroded by the electrolyte. At the same time, the quaternary ammonium salt cations in the synergistic structure induce uniform lithium deposition and inhibit dendrite growth, further improving the electrode's resistance to electrolyte corrosion; on the third aspect, the compound structure shown in formula I of the present application contains a large amount of nitrogen elements, which enhances the flame retardant properties of the electrolyte.
[0016] In addition, the present application can prevent the corrosion resistance of the electrode from being weakened by regulating the mass ratio of lithium alginate and the compound shown in formula I. The reason may be that lithium alginate and the compound shown in formula I are easily cross-linked by hydrogen bonds, which increases the steric effect of the compound shown in formula I, thereby causing the ability of the compound shown in formula I to load the electrode to decrease, thereby reducing the corrosion resistance of the lithium-ion battery electrode.
[0017] In some embodiments, the method for preparing the compound represented by formula I comprises the following steps:
[0018] (1) mixing p-aminobenzenesulfonic acid with an ice-water mixture and stirring, adding solid lithium hydroxide thereto and maintaining the temperature at 5-10° C. until the p-aminobenzenesulfonic acid is completely dissolved, thereby obtaining a p-aminobenzenesulfonic acid solution;
[0019] (2) Dissolve cyanuric chloride in anhydrous ethanol and cool to 5-10°C, then dropwise add the p-aminobenzenesulfonic acid solution in step (1) to adjust the pH of the system to neutral until the pH no longer changes. After filtering, the filtrate is concentrated under reduced pressure and then extracted with an organic solvent. The aqueous phase is freeze-dried to obtain a compound of formula II.
[0020] (II);
[0021] (3) Mix the compound represented by formula II in step (2) with anhydrous ethanol, add a tertiary amine compound, stir at room temperature for 18 to 20 hours, concentrate under reduced pressure to dry, wash, concentrate under reduced pressure to dry, and perform column chromatography to obtain a compound represented by formula III
[0022] (III);
[0023] (4) Molecular sieves and cesium hydroxide are added to N,N-dimethylformamide and ultrasonically stirred for 20 to 30 minutes. Then, an amino-terminated multi-branched hydroxy compound is added and stirred for 30 to 40 minutes. Subsequently, the compound represented by formula III in step (3) is added to the system and stirred at room temperature for 20 to 22 hours. After the reaction is completed, the system is filtered, concentrated under reduced pressure, dried, and subjected to column chromatography to obtain a compound represented by formula I.
[0024] In some embodiments, in step (1), the mass ratio of the p-aminobenzenesulfonic acid to the ice-water mixture is 1:(18-20).
[0025] Preferably, in step (1), the mass ratio of the p-aminobenzenesulfonic acid to the ice-water mixture is 1:19.
[0026] The present application can prevent the excessive concentration of p-aminobenzenesulfonic acid from causing polymerization with cyanuric chloride in step (2) by regulating the mass ratio of p-aminobenzenesulfonic acid to ice-water mixture, thereby increasing the quaternary ammonium salt structure therein, causing the electrolyte pH to be unstable and thus reducing the battery conductivity.
[0027] In some embodiments, in step (1), the molar ratio of p-aminobenzenesulfonic acid to lithium hydroxide is 1:(1.2-1.4).
[0028] In some embodiments, the molar ratio of cyanuric chloride in step (2) to p-aminobenzenesulfonic acid in step (1) is 1:(0.9-1).
[0029] Preferably, the molar ratio of cyanuric chloride in step (2) to p-aminobenzenesulfonic acid in step (1) is 1:0.95.
[0030] The applicant can make one of the halogens in cyanuric chloride react with p-aminobenzenesulfonic acid by adjusting the molar ratio of cyanuric chloride to p-aminobenzenesulfonic acid, thereby preventing more halogens from reacting with p-aminobenzenesulfonic acid, which results in a significant decrease in product activity and is not conducive to subsequent reaction with tertiary amine compounds.
[0031] In some embodiments, in step (3), the molar ratio of the compound represented by formula II to the tertiary amine compound is 1:(0.9~1).
[0032] Preferably, in step (3), the molar ratio of the compound represented by formula II to the tertiary amine compound is 1:0.95.
[0033] In some embodiments, in step (3), the tertiary amine compound has the following structure:
[0034] ;
[0035] Wherein R4, R5 and R6 are independently C1~C4 alkyl groups.
[0036] In some embodiments, in step (4), the molecular sieve is 4A zeolite molecular sieve.
[0037] In some embodiments, in step (4), the molar ratio of the cesium hydroxide, the amino-terminated multi-branched hydroxy compound and the compound represented by formula III is 1:(0.9-1.1):(1.1-1.3).
[0038] Preferably, in step (4), the molar ratio of the cesium hydroxide, the amino-terminated multi-branched hydroxy compound and the compound represented by formula III is 1:1:1.2.
[0039] In some embodiments, in step (4), the amino-terminated multi-branched hydroxy compound has the following structure:
[0040] ;
[0041] Wherein R1, R2, and R3 are independently C1~C3 alkyl hydroxyl groups.
[0042] In some embodiments, the solvent is a mixture of anhydrous ethanol and deionized water, and the mass ratio of the two is 1:(0.5~0.7).
[0043] In some embodiments, the phosphate compound is tris(trimethylsilyl)phosphate or triethyl phosphate.
[0044] On the other hand, the present invention provides a method for preparing a phosphoric acid-based electrolyte additive, comprising the following steps: mixing a phosphate compound, lithium alginate, a compound represented by formula I and a solvent into a slurry, and then drying at 70-80° C. for 24-28 hours to solidify and form the phosphate-based electrolyte additive.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The phosphate-based electrolyte additive of the present invention is prepared by curing and molding a phosphate ester compound, lithium alginate, a compound represented by formula I and a solvent. The additive can improve the battery cycle performance, prevent electrode corrosion, improve the flame retardancy of the phosphate-based electrolyte and improve the battery conductivity.
[0047] (2) In the first aspect, the compound represented by Formula I of the present invention contains a large number of hydroxyl groups in its structure, which can adsorb lithium ions well and provide an additional pathway for the transport of lithium ions, making its flux more uniform; in the second aspect, since the compound represented by Formula I contains a large number of quaternary ammonium salt structures, it can be loaded on the surface of the electrode to form an SEI film to prevent it from being corroded by the electrolyte. At the same time, the quaternary ammonium salt cations in the synergistic structure induce uniform lithium deposition and inhibit dendrite growth, further improving the electrode's resistance to electrolyte corrosion; in the third aspect, the compound represented by Formula I of the present application contains a large amount of nitrogen elements, which enhances the flame retardant properties of the electrolyte.
[0048] (3) The present invention can prevent the corrosion resistance of the electrode from being weakened by using lithium alginate and the compound shown in formula I in a specific mass ratio. The reason may be that lithium alginate and the compound shown in formula I are easily cross-linked by hydrogen bonds, which increases the steric effect of the compound shown in formula I, thereby causing the ability of the compound shown in formula I to load the electrode to decrease, thereby reducing the corrosion resistance of the lithium ion battery electrode. DETAILED DESCRIPTION
[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Preparation Example 1
[0051] The preparation method of the compound represented by formula I comprises the following steps:
[0052] (Ⅰ)
[0053] (1) 40 mmol of p-aminobenzenesulfonic acid was mixed with 130 mL of ice-water mixture and stirred, and 52 mmol of lithium hydroxide solid was added thereto while maintaining the temperature at 7°C until the p-aminobenzenesulfonic acid was completely dissolved to obtain a p-aminobenzenesulfonic acid solution;
[0054] (2) 42 mmol of cyanuric chloride was dissolved in 8 mL of anhydrous ethanol and cooled to 7°C. The p-aminobenzenesulfonic acid solution in step (1) was then added dropwise at a rate of 8 mL / min. The pH of the system was adjusted to 7 with a lithium hydroxide solution having a mass concentration of 15% until the pH no longer changed. After filtering, the filtrate was concentrated under reduced pressure and then extracted with an organic solvent. The aqueous phase was freeze-dried to obtain a compound of formula II.
[0055] (II);
[0056] (3) 40 mmol of the compound represented by formula II in step (2) was mixed with 120 mL of anhydrous ethanol, 38 mmol of triethylamine was added, and the mixture was stirred at 27°C for 19 h. The mixture was concentrated under reduced pressure and dried, and then washed with petroleum ether, concentrated under reduced pressure and dried, and subjected to column chromatography to obtain a compound represented by formula III
[0057] (III);
[0058] (4) Add 10 g of 4A molecular sieve and 34 mmol of cesium hydroxide to 160 mL of N,N-dimethylformamide and stir ultrasonically for 25 min. Then add 34 mmol of tris(hydroxymethyl)aminomethane and continue stirring for 35 min. Then add 40 mmol of the compound represented by formula III in step (3) to the system and stir at 27°C for 21 h. After the reaction is completed, filter, concentrate under reduced pressure, dry and pass through column chromatography to obtain the compound represented by formula I.
[0059] Preparation Example 2
[0060] The preparation method of the compound shown in Formula I is the same as that of Preparation Example 1, except that an equal molar amount of tri-n-butylamine is used instead of triethylamine, and an equal molar amount of 4-amino-4-(3-hydroxypropyl)-1,7-heptanediol is used instead of tris(hydroxymethyl)aminomethane, to obtain the compound shown in Formula I with the following structural formula:
[0061] (Ⅰ).
[0062] Preparation Example 3
[0063] The method for preparing the derivative of the compound represented by Formula I is the same as that in Preparation Example 1, except that in step (1), the amount of ice-water mixture added is 80 mL.
[0064] Preparation Example 4
[0065] The method for preparing the derivative of the compound represented by Formula I is the same as that of Preparation Example 1, except that in step (2), the amount of cyanuric chloride is 28 mmol.
[0066] Preparation Example 5
[0067] The preparation method of the derivative of the compound represented by Formula I is the same as that of Preparation Example 1, except that an equal molar amount of tert-butylamine is used instead of tris(hydroxymethyl)aminomethane.
[0068] Example 1
[0069] A phosphoric acid-based electrolyte additive comprises the following raw materials: tris(trimethylsilyl)phosphate, lithium alginate, a compound represented by formula I and a solvent, wherein the mass ratio of tris(trimethylsilyl)phosphate, lithium alginate, the compound represented by formula I and the solvent is 0.4:1:2:8; the structure of the compound represented by formula I is:
[0070] (I).
[0071] Wherein, the compound represented by formula I is prepared by Preparation Example 1, and the solvent is a mixture of anhydrous ethanol and deionized water, and the mass ratio of the two is 1:0.6.
[0072] The preparation method of the phosphoric acid-based electrolyte additive of this embodiment comprises the following steps: tri(trimethylsilyl)phosphate, lithium alginate, the compound shown in formula I and a solvent are mixed into a slurry and then placed in a slurry for drying at 75°C for 26 hours to solidify and form, thereby obtaining the phosphoric acid-based electrolyte additive.
[0073] Example 2
[0074] A phosphoric acid-based electrolyte additive comprises the following raw materials: tris(trimethylsilyl)phosphate, lithium alginate, a compound represented by formula I and a solvent, wherein the mass ratio of tris(trimethylsilyl)phosphate, lithium alginate, the compound represented by formula I and the solvent is 0.3:1:1.5:6; the structure of the compound represented by formula I is:
[0075] (I).
[0076] Wherein, the compound represented by formula I is prepared by Preparation Example 1, and the solvent is a mixture of anhydrous ethanol and deionized water, and the mass ratio of the two is 1:0.5.
[0077] The preparation method of the phosphoric acid-based electrolyte additive of this embodiment comprises the following steps: tri(trimethylsilyl)phosphate, lithium alginate, the compound shown in formula I and a solvent are mixed into a slurry and then placed in a slurry for drying at 70°C for 28 hours to solidify and form, thereby obtaining the phosphoric acid-based electrolyte additive.
[0078] Example 3
[0079] A phosphoric acid-based electrolyte additive comprises the following raw materials: tris(trimethylsilyl)phosphate, lithium alginate, a compound represented by formula I and a solvent, wherein the mass ratio of tris(trimethylsilyl)phosphate, lithium alginate, the compound represented by formula I and the solvent is 0.5:1:2.5:10; the structure of the compound represented by formula I is:
[0080] (I).
[0081] Wherein, the compound represented by formula I is prepared by Preparation Example 1, and the solvent is a mixture of anhydrous ethanol and deionized water, and the mass ratio of the two is 1:0.7.
[0082] The preparation method of the phosphoric acid-based electrolyte additive of this embodiment comprises the following steps: tri(trimethylsilyl)phosphate, lithium alginate, the compound shown in formula I and a solvent are mixed into a slurry and then placed in a slurry for drying at 80°C for 24 hours to solidify and form, thereby obtaining the phosphoric acid-based electrolyte additive.
[0083] Example 4
[0084] A phosphoric acid-based electrolyte additive comprises the following raw materials: tris(trimethylsilyl)phosphate, lithium alginate, a compound represented by formula I and a solvent, wherein the mass ratio of tris(trimethylsilyl)phosphate, lithium alginate, the compound represented by formula I and the solvent is 0.5:1:2.5:10; the structure of the compound represented by formula I is:
[0085] (I).
[0086] Wherein, the compound represented by Formula I is prepared by Preparation Example 2, and the solvent is a mixture of anhydrous ethanol and deionized water, and the mass ratio of the two is 1:0.6.
[0087] The preparation method of the phosphoric acid-based electrolyte additive of this embodiment comprises the following steps: tri(trimethylsilyl)phosphate, lithium alginate, the compound shown in formula I and a solvent are mixed into a slurry and then placed in a slurry for drying at 75°C for 26 hours to solidify and form, thereby obtaining the phosphoric acid-based electrolyte additive.
[0088] Example 5
[0089] A phosphoric acid-based electrolyte additive and a preparation method thereof. The specific implementation method is the same as Example 1, except that an equal mass of a derivative of the compound represented by Formula I is used to replace the compound represented by Formula I, and the derivative of the compound represented by Formula I is prepared by Preparation Example 3.
[0090] Example 6
[0091] A phosphoric acid-based electrolyte additive and a preparation method thereof. The specific implementation method is the same as Example 1, except that an equal mass of a derivative of the compound represented by Formula I is used to replace the compound represented by Formula I, and the derivative of the compound represented by Formula I is prepared by Preparation Example 4.
[0092] Example 7
[0093] A phosphoric acid-based electrolyte additive and a preparation method thereof. The specific implementation method is the same as Example 1, except that an equal mass of a derivative of the compound represented by Formula I is used to replace the compound represented by Formula I, and the derivative of the compound represented by Formula I is prepared by Preparation Example 5.
[0094] Performance Testing:
[0095] The preparation of the lithium battery refers to the patent disclosed in CN115241532B, wherein the electrolyte is lithium hexafluorophosphate, and the electrolyte additive is the phosphoric acid-based electrolyte additive prepared in each embodiment of the present application. The obtained lithium battery is tested according to the following method:
[0096] (1) Cycle performance: The lithium-ion battery is placed in an environment of 25°C, with a cycle rate of 1C and a charging voltage of 3V. The initial capacity of the lithium-ion battery is recorded as D0. The capacity of the lithium ion after 1000 cycles of charge and discharge at the aforementioned temperature and charging voltage is recorded as D1. The capacity retention rate (%) is calculated according to the following formula:
[0097] Capacity retention rate (%) = D1 / D0 × 100%;
[0098] (2) Conductivity: Use DDSJ-318T conductivity meter to test battery conductivity;
[0099] (3) Flame retardant test: The electrolyte additive is exposed to a fire source to test its combustion performance.
[0100] The test results are shown in Table 1.
[0101] Table 1
[0102]
[0103] According to the data in Table 1, the phosphoric acid-based electrolyte additives prepared in Examples 1 to 4 have good flame retardancy, cycle performance and conductivity; in Example 5, due to the change in the mass ratio of p-aminobenzenesulfonic acid to the ice-water mixture, polymerization occurs in the reaction, and the quaternary ammonium salt structure per unit molecule increases, resulting in unstable electrolyte pH, thereby reducing the battery conductivity; in Example 6, due to the change in cyanuric chloride and p-aminobenzenesulfonic acid, most of the halogen groups in cyanuric chloride react, reducing the quaternary ammonium salt structure, thereby reducing the corrosion resistance of the electrode and the battery cycle performance; in Example 7, due to the use of equimolar tert-butylamine instead of tris(hydroxymethyl)aminomethane, the hydroxyl group in the phosphoric acid-based electrolyte additive is reduced, the content of lithium ions adsorbed on the electrolyte is reduced, and the lithium ion transmission performance is reduced, thereby reducing the conductivity of the lithium battery.
[0104] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A phosphoric acid-based electrolyte additive, characterized in that: The invention comprises the following raw materials: a phosphate compound, lithium alginate, a compound represented by formula I and a solvent, wherein the mass ratio of the phosphate compound, lithium alginate, the compound represented by formula I and the solvent is (0.3-0.5):1:(1.5-2.5):(6-10); The structure of the compound shown in Formula I is: (I), where R is , is a bond connecting the amino group, R1, R2, and R3 are independently C1~C3 alkyl hydroxyl groups, and R4, R5, and R6 are independently C1~C4 alkyl groups.
2. A phosphoric acid-based electrolyte additive according to claim 1, characterized in that: The preparation method of the compound represented by formula I comprises the following steps: (1) mixing p-aminobenzenesulfonic acid with an ice-water mixture and stirring, adding solid lithium hydroxide thereto and maintaining the temperature at 5-10° C. until the p-aminobenzenesulfonic acid is completely dissolved, thereby obtaining a p-aminobenzenesulfonic acid solution; (2) Dissolve cyanuric chloride in anhydrous ethanol and cool to 5-10°C, then dropwise add the p-aminobenzenesulfonic acid solution in step (1) to adjust the pH of the system to neutral until the pH no longer changes. After filtering, the filtrate is concentrated under reduced pressure and then extracted with an organic solvent. The aqueous phase is freeze-dried to obtain a compound of formula II. (II); (3) Mix the compound represented by formula II in step (2) with anhydrous ethanol, add a tertiary amine compound, stir at room temperature for 18 to 20 hours, concentrate under reduced pressure to dry, wash, concentrate under reduced pressure to dry, and perform column chromatography to obtain a compound represented by formula III (Ⅲ); (4) Molecular sieves and cesium hydroxide are added to N,N-dimethylformamide and ultrasonically stirred for 20 to 30 minutes. Then, an amino-terminated multi-branched hydroxy compound is added and stirred for 30 to 40 minutes. Subsequently, the compound represented by formula III in step (3) is added to the system and stirred at room temperature for 20 to 22 hours. After the reaction is completed, the system is filtered, concentrated under reduced pressure, dried, and subjected to column chromatography to obtain a compound represented by formula I.
3. A phosphoric acid-based electrolyte additive according to claim 2, characterized in that: In step (1), the mass ratio of the p-aminobenzenesulfonic acid to the ice-water mixture is 1:(18-20).
4. A phosphoric acid-based electrolyte additive according to claim 2, characterized in that: The molar ratio of cyanuric chloride in the step (2) to p-aminobenzenesulfonic acid in the step (1) is 1:(0.9-1).
5. A phosphoric acid-based electrolyte additive according to claim 2, characterized in that: In step (3), the molar ratio of the compound represented by formula II to the tertiary amine compound is 1:(0.9-1).
6. A phosphoric acid-based electrolyte additive according to claim 2, characterized in that: In step (3), the tertiary amine compound has the following structure: ; Wherein R4, R5 and R6 are independently C1~C4 alkyl groups.
7. A phosphoric acid-based electrolyte additive according to claim 2, characterized in that: In step (4), the molar ratio of the cesium hydroxide, the amino-terminated multi-branched hydroxy compound and the compound represented by formula III is 1:(0.9-1.1):(1.1-1.3).
8. A phosphoric acid-based electrolyte additive according to claim 2, characterized in that: In step (4), the structure of the amino-terminated multi-branched hydroxy compound is as follows: ; Wherein R1, R2, and R3 are independently C1~C3 alkyl hydroxyl groups.
9. A phosphoric acid-based electrolyte additive according to claim 1, characterized in that: The phosphate compound is tris(trimethylsilyl)phosphate or triethyl phosphate.
10. A method for preparing the phosphoric acid-based electrolyte additive according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing a phosphate compound, lithium alginate, a compound shown in formula I and a solvent into a slurry, and then drying at 70-80° C. for 24-28 hours to solidify and form the mixture, thereby obtaining a phosphate-based electrolyte additive.
Citation Information
Patent Citations
Lithium alginate for use as an additive in lithium batteries, its preparation method and application
CN114430042B
Preparation and application of a solid electrolyte and its additives
CN114530629B
Electrolyte additives, electrolytes, and lithium batteries
CN115241532B
Electrolyte additive, electrolyte and solar cell thereof
CN102789902A
Battery electrolyte and preparation method of benzenesulfonate compound in battery electrolyte
CN113851711A